Real-time Monitoring of Suspended Particulate Matter in Indoor Air: Validation and Application of a Light-scattering Sensor - Anna Susz; Pascal Pratte; Catherine Goujon-Ginglinger (Aerosol and Air Quality Research)
Abstract Since the 1950s, awareness of the impact of air pollution on human health has been growing. Of the many recognized air pollutants, suspended particulate matter has received the most attention, as both PM2.5 and PM10 can affect humans upon inhalation. Consequently, PM monitoring is critical to linking indoor pollution and exposure, and a validated measuring instrument is essential. Portable monitors, which track temporal changes in the aerosol mass concentration in real time, are a faster alternative to offline gravimetric techniques, which provide only averaged values. Hence, this study evaluated the performance of the DustTrak DRX aerosol monitor in assessing indoor air quality and validated its ability to measure complex aerosols. Three DustTrak units were used to measure different aerosols, e.g., ambient air, polystyrene latex (PSL) spheres, and environmental tobacco smoke (ETS), and the results were compared to those obtained with the standard gravimetric method. Notably, the bias of the DustTrak relative to the gravimetric method for ETS measurements ranged from 2% to 15% when a photometric calibration factor (PCF) of 0.38 was applied. Additionally, the working range of the tested units was established, and the limits of detection and quantification were found to be 5 and 15 µg m−3, respectively. Finally, in order to serve as an alternative to the gravimetric method, these instruments must be accredited for PM measurement in accordance with standards such as ISO 17025.